PKM PEMBERDAYAAN PROGRESIF SCIENCE AND INNOVATION DAN MANAJEMEN INTERNATIONAL COMPETITION BAGI SANTRI DAN GURU SMA PROGRESIF BUMI SHALAWAT - wahyu sabtiawan; Fida Rachmadiarti; Sifak Indana; Nadi Suprapto (Universitas Negeri Surabaya, 2022)
In 2021, Unesa PKM Team provided guidance to Bumi Shalawat Progressive High School teachers regarding making competition management and conducting trials on Bumi Shalawat Progressive High School students through internal competitions. Starting from the PKM application letter from the pesantren partner (the principal of SMA Bumi Shalawat) to Unesa, then follow-up activities were carried out and an activity was planned with the title,